Taide ja liike työelämän kehittämisessä - Jussila, Petri; Lehtoranta, Petri; Jussila, Petri; Saarela, Jyrki; Hirvanen, Matti; Purokuru, Vesa; Häyrynen, Teija; Jyväskylän ammattikorkeakoulu. Hyvinvointiyksikkö (Jyväskylän ammattikorkeakoulun julkaisuja, ISSN 1456-2332, 2014)
There is many issues which we must solve if we want our work places to be healthy and productive in the future. The key questions are: How you can support our employees for creativity and courage? How you can support our teams to co-create, discuss openly and think innovative? How you can share leadership? How you can create connection between individual’s personality and organization's common values? TAI LIIKU -project has found new kind of solutions to these issues. Project has implemented in the region of Central Finland. The project has funded by European Social Fund. JAMK University of applied sciences has coordinated the project. Humap Ltd and Central Finland Sport Federation are the partners of the project. The project´s network consists lots of artists, producers, sports experts, developers and consultants. The project´s main goal is co-create new arts and sports based services for better working life and to support organizations know-how about the subject. The project have co-created new arts and sports based services for better working life. The results of the project prove that it is reasonable to develop the working life with the help of the creative methods and processes.
Keywords: Humap Oy : Jyväskylä; Landis&Gyr Oy : Jyväskylä; luovat menetelmät; liikunta; taidelähtöiset menetelmät; taide; työelämä; työyhteisöt; johtaminen; organisaatioilmasto; työhyvinvointi; jaksaminen; innovatiivisuus; kehittäminen; kreativa metoder; motion; konstbaserade metoder; konst; arbetsliv; arbetsgemenskaper; ledarskap (verksamhetsledning); organisationsklimat; välbefinnande i arbetet; ork; innovativitet; utveckling (verksamhet)